Pengaruh Pemberian Terapi Pepaya Mengkal Dan Terapi Otot Progresif Pada Pasien Hipertensi Kelurahan Pondok Rangon - Riani, Novariani; Alita, Riadinni; Setiarini, Tatik (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Hypertension, often referred to as the “silent killer”, is a serious health problem that requires effective treatment. This study aims to analyze the effect of giving papaya juice therapy and progressive muscle relaxation in reducing blood pressure in hypertensive patients in PondokRanggon Village. The method used is quantitative with a Pre-Experimental design and a one group pre-test dan post-test approach. A total of 30 respondents were divided into two groups: 15 people were given papaya mengkal juice therapy and 15 others received progressive muscle relaxation therapy. The results showed a significant reduction in systolic and diastolic blood pressure in both intervention group, with p < 0.05. Thus, papaya juice therapy and effective in lowering blood pressure in hypertensive patients, as well as offering a non-pharmacological alternative that is safe and can be applied in everyday life.